Implementasi Kebijakan Penerbitan Izin Usaha Mikro Kecil di Kecamatan Teluk Nibung Kota Tanjungbalai - Ali, Muhammad; Nasution, Arif; Mardiana, Siti (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2019)
The purpose of this study is to analyze the implementation of the policy for issuing permits for micro and small businesses in the Teluk Nibung District Office. This type of research is descriptive qualitative, according to Nawawi (2010: 57) Qualitative descriptive research is research that seeks a causal relationship between two or more variables of several populations or samples with random sampling techniques and uses research instruments in data collection to test hypotheses / allegations that have been set with several questions. The results of the study found that publishing was still very slow and used a long time and inadequate supporting facilities. The next problem is that communication between the implementor and the community of micro and small business actors is still lacking, where the socialization carried out by sub-district officials to the community has not been maximized so that most micro and small business actors do not know what benefits can be enjoyed from the business permit, and even some the community of micro and small businesses do not yet know about the policy that the making of micro and small business permits can already be done at the District / Kelurahan office.